Computational Drug Design in Problem-Based Learning: A Pedagogical Experience in Pre-Service Chemistry Teachers - Rodríguez-Becerra, Jorge; Hernández-Ramos, José; Cáceres-Jensen, Lizethly; Druker Ibáñez, Sofía (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
In this presentation Prof. Jorge Rodríguez-Becerra et al. presents how to use modern research as a context for problem-based learning in pre-service chemistry teacher education.